Analysis of New Loleo Airport Facilities in Tidore City Islands - Sudirman Hi Umar; Muhammad Taufiq Y.S; Nurmaiyasa Marsaoly (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The construction of a new airport in Loleo Tidore Islands City acts as a transportation network node and supports economic growth and local government activities in North Maluku, that this airport is projected for the connectivity of the IWIP Industrial Estate and the capital of North Maluku Province (Sofifi City). The data collection methods used in this study include observation and literature study. The analyzed facilities consist of airside facilities consisting of a runway, taxiway, and apron. While the land-side facilities to be analysed consist of facilities in public zones, technical zones, and supporting zones. Other facilities that will be analysed also in this study consist of flight navigation facilities, visual landing aids, communication and information facilities, PKP-PK facilities, and PLLU facilities. The results of the analysis of total land requirements for the construction of new airport facilities in Loleo City Tidore Islands phase 1 amounted to 200 Ha and phase 2 amounted to 200 Ha so the total land needed was 400 Ha. The annual passenger movement of Phase I amounted to 569,443 passengers in Phase II amounted to 1,175,839 passengers, the plan the length of the runway Phase I along 1600 m served the largest aircraft ATR 72-600, and phase II 2500 m served the largest aircraft, namely Boeing 737-900 ER, and the farthest route of phase I development was Loleo - Ambon and the farthest route of phase II development was Loleo – Jakarta.